The complete chloroplast genome of Actinidia fulvicoma. Issue 2 (3rd July 2019) - Zhang, Fuquan; Yan, Zhihao; Xu, Yiqing; Lin, Haifeng
Abstract: The species of genus Actinidia are economically and nutritionally important fruits with remarkably high vitamin C content. Here, we assembled and characterized the complete chloroplast (cp) genome sequence of Actinidia fulvicoma ( A. fulvicoma ) using Illumina paired-end sequencing data. The cp genome is 157, 339 bp in length, including a large single-copy region (LSC) of 88, 741 bp, a small single-copy region (SSC) of 20, 512 bp, and a pair of 24, 043 bp inverted repeat (IR) regions. A total of 131 genes, consisting of 85 protein-coding genes, 38 tRNA genes, and 8 rRNA genes, were annotated in the A. fulvicoma cp genome. Phylogenetic analysis confirmed the evolutionary position of A. fulvicoma within the genus Actinidia .